2015
DOI: 10.3944/aott.2015.14.0274
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for postoperative deformity in thoracolumbar burst fractures. A statistical approach.

Abstract: All valid regression models displayed modest explanatory power, suggesting that factors other than those taken into consideration are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is necessary to further investigate whether the insufficient muscular strength and poor control provided by the fatty infiltration of the LMM is the cause of LBP or vice versa. Recent studies have shown that atrophy and muscle weakening give rise to disc degeneration and cause pain and instability of the spine but other causes such as trauma are also incriminated [17, 18]. Furthermore it would be useful to confirm whether fat infiltration in the lumbar LMM is reversible and if so, to confirm the study of Kim, et al that the reversibility coincides with improvement of symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to further investigate whether the insufficient muscular strength and poor control provided by the fatty infiltration of the LMM is the cause of LBP or vice versa. Recent studies have shown that atrophy and muscle weakening give rise to disc degeneration and cause pain and instability of the spine but other causes such as trauma are also incriminated [17, 18]. Furthermore it would be useful to confirm whether fat infiltration in the lumbar LMM is reversible and if so, to confirm the study of Kim, et al that the reversibility coincides with improvement of symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…3 In 1983, Francis Denis popularized the concept of middle column by dividing it into three columns, a concept widely used today. 1,3,17,21,24,25,33,34 Several other classifications have emerged since then. McCormack, in 1994, noted that some cases of burst fracture surgically treated with short-segment fixation did not present a good outcome and created a new classification called LSC.…”
Section: Discussionmentioning
confidence: 99%
“…It was only in 1970 that Sir Frank introduced the concept of two columns, describing the burst fracture for the first time 3 . In 1983, Francis Denis popularized the concept of middle column by dividing it into three columns, a concept widely used today 1,3,17,21,24,25,33,34 . Several other classifications have emerged since then.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some degree of deformity is common after spine trauma, regardless of the treatment. 2-13 According to White et al and Whitesides, even a small degree of kyphosis, by increasing the moment arm, can lead to a progressive deformity over the years 14,15 ; however, at which point a posttraumatic deformity of the spine becomes clinically “relevant” or symptomatic is still up for debate. This “Spinal Posttraumatic Deformity” (SPTD) can require extensive surgery with high risk of complications and is more aggressive than treatment of the primary injury itself.…”
Section: Introductionmentioning
confidence: 99%